The role of silane gas flow rate on PECVD-assisted fabrication of silicon nanowires - Hamidinezhad, H. (Springer Verlag, 2016)
Silicon (Si) core–shell nanowires (NWs) were successfully prepared by very high frequency plasma-enhanced chemical vapor deposition technique, and the effect of silane (SiH4) gas flow rates on physicochemical properties of silicon NWs was investigated. Field emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectroscopy, transmission electron microscopy (TEM), X-ray diffraction (XRD) and Raman spectroscopy were used to characterize SiNWs. Structural properties and morphology of NWs were studied as a function of SiH4 gas flow rate. Microscopic analysis revealed the formation of SiNWs with average tip and stem diameters ranging from 18 to 30 and 21 to 67 nm, respectively. Furthermore, the average length of Si NWs calculated based on the FESEM images was about 300–1800 nm. We have found that the growth of SiNWs increased with increasing in SiH4 gas flow rate. XRD, Raman spectra in addition to high-resolution TEM, verified the formation of crystalline SiNWs. A possible growth mechanism was suggested based on our observations.